Imaging findings in Erdheim-Chester disease: what every radiologist needs to know - Kumar, Pawan; Singh, Anuradha; Gamanagatti, Shivanand; Kumar, Sanjeev; Chandrashekhara, Sheragaru Hanumanthappa (Polish Journal of Radiology, 2018)
Erdheim-Chester disease (ECD) is a rare sporadic non-Langerhans cell histiocytic (LCH) proliferative disorder with systemic predilection. It usually affects adults in the 5th-7th decades of life and has non-specific clinical manifestations. Its suspicion is often heralded by the presence of characteristic radiological findings and subsequently confirmed by demonstration of CD68-positive xanthogranulomatous infiltrates on histopathology. Despite being a non-malignant entity, it might be fatal due to organ dysfunction. Imaging plays a key role in the diagnosis, management, and follow-up. Imaging findings are essential to establish the diagnosis, assess actual disease burden, and explore the aetiopathogenesis and therapeutic options to halt disease progression and associated morbidity.